2017
DOI: 10.1136/archdischild-2016-311233
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of prenatally diagnosed congenital cystic lung lesions: long-term follow-up of 119 cases

Abstract: This is one of the largest case series documenting the natural history of CPAMs and PS following a prenatal diagnosis and demonstrates that conservative management is a reasonable option in selected cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
70
0
10

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(84 citation statements)
references
References 42 publications
4
70
0
10
Order By: Relevance
“…The optimal management strategy in asymptomatic CLM remains debatable . In this study, more than half of the children with CLM did not require surgical resection, which is consistent with a previous study that advocated a watchful waiting approach . When only looking at the infants who had been diagnosed prenatally, it appears that approximately two‐thirds (ie 29/47, 62%) could be managed observationally.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The optimal management strategy in asymptomatic CLM remains debatable . In this study, more than half of the children with CLM did not require surgical resection, which is consistent with a previous study that advocated a watchful waiting approach . When only looking at the infants who had been diagnosed prenatally, it appears that approximately two‐thirds (ie 29/47, 62%) could be managed observationally.…”
Section: Discussionsupporting
confidence: 87%
“…A previous study at our center showed airflow obstruction in approximately one‐third of children with CLM at the ages of 6 and 12 months, both in those who had required surgery and in those who remained asymptomatic . The data on the long‐term outcome are scarce, especially in children with asymptomatic CLM …”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, the advent of prenatal diagnosis also made it possible to evaluate outcome in a series of children with CPM, including asymptomatic cases, improving our understanding of the natural course of CPM and calling into question the systematic recourse to surgery. The paper by Cook et al 1 in this issue further extends our knowledge. It describes the outcome of 119 children with prenatally diagnosed CPM followed at a single centre for a median of 9.9 years.…”
supporting
confidence: 68%
“…There is a clear need for more evidence as to how to deal with asymptomatic congenital thoracic malformations (CTMs), and thus the recent series from Great Ormond Street Hospital1 and the accompanying editorial2 are to be welcomed; however, the evidence review is incomplete. The risk of complications in non-operated CTMs after the postnatal period over around a decade was estimated at 3.2% in a meta-analysis 3.…”
mentioning
confidence: 99%